The Gold Standard Programme: smoking cessation interventions for disadvantaged smokers are effective in a real-life setting. Issue 6 (16th June 2012) - Neumann, Tim; Rasmussen, Mette; Ghith, Nermin; Heitmann, Berit L; Tønnesen, Hanne
Abstract : Objectives: To evaluate the real-life effect of an evidence-based Gold Standard Programme (GSP) for smoking cessation interventions in disadvantaged patients and to identify modifiable factors that consistently produce the highest abstinence rates. Design: Observational prospective cohort study. Setting: GSPs in pharmacies, hospitals and communities in Denmark, reporting to the national Smoking Cessation Database. Participants: Disadvantaged patients, defined as patients with a lower level of education and those receiving unemployment benefits. Interventions: 6-week manualised GSP smoking cessation interventions performed by certified staff. Main outcome measures: 6 months of continuous abstinence, response rate: 80%. Results: Continuous abstinence of the 16 377 responders was 34% (of all 20 588 smokers: 27%). Continuous abstinence was lower in 5738 smokers with a lower educational level (30% of responders and 23% of all) and in 840 unemployed (27% of responders and 19% of all). In respect to modifiable factors, continuous abstinence was found more often after programmes in one-on-one formats (vs group formats) among patients with a lower educational level, 34% (vs 25%, p=0.037), or among unemployed, 35% (vs 24%, p=0.099). The variable 'format' stayed in the final model of multivariable analyses in patients with a lower educational level, OR=1.31 (95% CI 1.05 to 1.63). Conclusions: Although continuous abstinence was lower among disadvantaged smokers, the absolute difference was small. If the programme had been as effective in disadvantaged as in non-disadvantaged groups, there would have been an extra 46 or 8 quitters annually, respectively. Promoting individual interventions among those with a low education may increase the effectiveness of GSP.